PARAMETERS OF THE HEMODYNAMIC AFTER ABLATION ATRIAL FIBRILLATION AND/OR FLUTTER DEPENDING ON THE FUNCTIONAL CLASS OF CHRONIC HEART FAILURE - Zolotarova, Tetyana; Bilchenko, Oleksander (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
Evaluated parameters of the hemodynamic before and after ablation atrial fibrillation and/or flutter depending on the functional class of chronic heart failure in 74 patients. It was found that patients with the I functional class of chronic heart failure have significantly lower left atrium size compared to III functional class, which is associated with the better efficiency of the radiofrequency ablation in the remote period. Patients with the I and III functional class of chronic heart failure are having increasement of QTc duration in acute period of radiofrequency ablation that could be used as an independent predictor of arrhythmia recurrence. Patients with the I functional class chronic heart failure who failed drug therapy for atrial fibrillation and/or flutter alternative treatment in the form of the radiofrequency ablation should be considered as choice therapy.The levels of heart rate and pulse decreases in I and III functional class of the chronic heart failure in the acute period radiofrequency ablation; systolic and diastolic blood pressure, QRS, left ventricle end-diastolic and left ventricle end-systolic diameter do not change after radiofrequency ablation.Patient I and III functional class of the chronic heart failure are having increasement of QTc duration in acute period of radiofrequency ablation that could be used as an independent predictor of arrhythmia recurrence.Patients with I functional class of the chronic heart failure have significantly lower left atrium size compared to III functional class of the chronic heart failure, which is associated with the best outcome of effectiveness of radiofrequency ablation in the late period.